A Study on Environmental Care Attitudes and Responsibilities in Science Learning among Elementary School Students: A Study on Environmental Care Attitudes and Responsibilities in Science Learning among Elementary School Students - Rahmi Novalita; Intan Deliana; Hamsidar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study was motivated by the low level of students’ environmental awareness and responsibility, the suboptimal implementation of school regulations, limited facilities, and minimal socialization at SD Negeri 28 Peusangan. The study aimed to describe the implementation of school programs in developing students’ environmental awareness and responsibility in Science Learning. This study employed a qualitative approach and was conducted at SD Negeri 28 Peusangan . Key informants consisted of teachers, students (Grades III and VI), and the principal. Data were collected through structured interviews, and were validated using source triangulation and member checking. Data analysis was carried out using qualitative descriptive methods, namely data reduction, data presentation and conclusions .The results showed that the program implementation was carried out systematically and hierarchically, supported by strong collaboration among school leadership policies, teacher mentoring, and active student participation. Students’ attitude transformation evolved from reactive compliance in lower grades to intrinsic awareness and proactive leadership in higher grades. The development strategies focused on integrating values through developmentally oriented habituation, combining role modeling with the provision of tangible facilities, and evolving from reward-based approaches to full trust and project-based responsibility in Science Learning. The core strategy was positioning students as agents of change, enabling responsibility to grow from a sense of ownership of the school environment.